Study of clinical, biochemical evaluation and outcome in hypertrophic pyloric stenosis - Kumar, Anil; Gupta, Umesh K.; Gupta, Prashant; Singh, Somendra Pal; Gupta, Mohit; Singh, Praveen; Prakash, Manas (International Journal of Contemporary Pediatrics, 2016)
Background: Gastric outlet obstruction (GOO) in infancy and childhood may result from congenital causes, antral diaphragm, pyloric atresia, heterotrophic pancreas, and infantile hypertrophic pyloric stenosis (IHPS), or acquired causes (peptic ulcer, caustic ingestion, tumour, chronic granulomatous disease and Eosinophilic gastroenteritis). Infantile hypertrophic pyloric stenosis (IHPS) is among the most common surgical disorders in infancy and presents in approximately 3:1000 live births in the United States. In India it is estimated to be 1 in 3,500 live births. The objective of the study was to analyse the age and sex of presentation, try to compare preoperative and postoperative biochemical alteration and find out how to reduce the incidence of complications of infantile hypertrophic pyloric stenosis (IHPS). Methods: Children attending at surgery OPD or emergency UP RIMS & R for no bilious vomiting during 15 March 2015 to 15 February 2016 less than 1 Year of age of both sex. Results: We found that IHPS was more common among first born male child in more commonly in Hindus and most common time of presentation is first 8 weeks dyselectronemia was a common feature. Conclusions: Infantile hypertrophic pyloric stenosis (IHPS) which is caused by thickened antropyloric muscle is a disease which causes gastric outlet obstruction. It is the most common surgical condition in infants within two month of postnatal life. This disease is presented with projectile non-bilious vomiting which may be blood tinged if it is prolonged without correction may cause hypochloremic hypokalemic alkalosis and death in more than 50% of the affected patients.